Cognitive and gait in Wilson’s disease: a cognitive and motor dual-task study - Wang, Gongqiang; Jin, Ping; Ma, Xinfeng; Hong, Xia; Zhang, Long; Lin, Kang; Wen, Xiao; Bai, Xue; Han, Yongzhu (Frontiers in Neurology, 2023)
Wilson's disease (WD) is a rare complex disorder of copper metabolism caused by ATP7B gene mutation, which leads to unregulated accumulation of copper in various tissues. It usually takes place in adolescence, and its clinical manifestations are progressive neuropsychiatric symptoms, liver cirrhosis, renal damage and Kayser-Fleischer ring.The results of this study showed that there were 32 (50.8%) patients with the neurologic type, 28 (44.4%) patients with cognitive impairment and 39 (61.9%) patients with abnormal brain MRI, which reflected the incomplete matching of cognitive impairment, neurologic type and abnormal brain MRI.Cognitive impairment in WD patients can be manifested in many cognitive fields of ACE-Ⅲ except language understanding. However, gait abnormality is related to many cognitive fields in ACE-Ⅲ, except attention, cognitive influence on gait is mainly reflected in the change of pace speed and step size. Under different cognitive motor tasks, WD patients with cognitive impairment showed gait speed and stride length (p<0.05), but not gait frequency (p>0.05). It can be seen that gait is also an outward manifestation of the overall cognitive impairment of WD patients, and the cognitive impairment of WD patients can be predicted by the gait performance parameters of pace speed and step size in the clinic. Under different cognitive motor tasks, WD patients with cognitive impairment showed gait speed and stride length (p<0.05), but not gait frequency (p>0.05). It shows that different cognitive-motor dual tasks will participate in influencing different gait performance parameters of WD patients.The results of this study show that brain atrophy, thalamic, caudate nucleus, and cerebellar were correlated with cognitive impairment (p<0.05). The lenticular nucleus is related to the step size,brain atrophy is related to the pace speed, thalamus, caudate nucleus, and midbrain are involved in step frequency in WD patients (p<0.05).WD patients had a high incidence of cognitive impairment and gait disorder, the pace speed and step size can reflect the cognitive impairment of WD patients. Cognitive impairment affects the gait disorder of WD patients, and the joint participation of cognitive impairment and lesion brain area may be the principal neural mechanism of gait abnormality in WD patients.